Learning style-based tactile materials as a tool to enhance the learning performance of high school science students - Vergara, H.P. (2003)
This action research focused on the use of tactile materials and their effects on the learning process of the high school science students. A pre-test/post-test type of research was conducted to determine the effect of tactile materials. A class composed of 20 students from a private school in Los Banos, Laguna was chosen as respondents. Majority of the respondents have high tactile preference. Using the significantly increased when compared to the pretest scores. This showed that the tactile materials helped increase the comprehension and the memory retention of the respondents. Only 10% of the class performed poorly in the posttest because of the research was only limited to the use of tactile materials. A more comprehensive study on the use of tactile materials. A more comprehensive study on the use of other elements in the classroom, included in the Dunn and Dunn Learning Style Model, is highly recommended.
Keywords: Learning strategies; Student performance; High school students